The paradox of pre-conviction punishment: the experience of living with bail conditions - Yule, Carolyn (Journal of crime and justice, 2023)
Conditional release on bail is often perceived as being more humane than the harsh reality of incarceration and, as such, the deprivations it imposes remain largely unexplored. Comparing life on bail to community sanctions allows us to extend current research on the effects of living with conditions before a conviction. By asking how are the punitive effects of bail experienced, we assess the ways in which 47 individuals accused of a crime navigate release with conditions. Interviews show that experiences vary along a continuum from being ‘it’s easy man’ all the way to ‘it’s like incarceration.’ Our findings help conceptualize the experiences of ‘punitiveness’ in the context of bail and indicate both the hidden costs and benefits of conditional release.